Outside bleaching in discolored teeth: a case series - Melendez, Diego (2023)
Dyschromia of teeth is a common clinical issue in dental practice, often posing an aesthetic concern that may impact the patient's self-esteem. While the internal bleaching technique usually offers favorable long-term outcomes, situations arise where chamber opening is not viable. In such instances, this case report highlights the application of external bleaching through both in-office and at-home methods. These techniques were employed to address darkened teeth, successfully restoring their natural color using a minimally invasive approach.